The Evolution of Digital Chemistry at Southampton. Issue 9 (September 2015) - Bird, Colin; Coles, Simon J.; Frey, Jeremy G.
Abstract In this paper we take a historical view of e‐Science and e‐Research developments within the Chemical Sciences at the University of Southampton, showing the development of several stages of the evolving data ecosystem as Chemistry moves into the digital age of the 21st Century. We cover our research on aspects of the representation of chemical information in the context of the world wide web (WWW) and its semantic enhancement (the Semantic Web) and illustrate this with the example of the representation of quantities and units within the Semantic Web. We explore the changing nature of laboratories as computing power becomes increasing powerful and pervasive and specifically look at the function and role of electronic or digital notebooks. Having focussed on the creation of chemical data and information in context, we finish the paper by following the use and reuse of this data as facilitated by the features provided by digital repositories and their importance in facilitating the exchange of chemical information touching on the issues of open and or intelligent access to the data.